The future of our radiation protection profession. (27th September 2021) - Bryant, Peter; Coates, Roger; Garnier-Laplace, Jacqueline; Guen, Bernard Le; Higley, Kathryn; Kim, Geehyun; Rousselet, Lelia; Salomaa, Sisko; Stewart, Joanne
Abstract: There is widespread recognition of the challenge of an ageing profession and the need to recruit, train and retain the next generation of radiation protection professionals. This challenge was the topic of a special session at the International Radiation Protection Association IRPA15 International Congress. It is necessary to address three key aspects: capturing the future professional: gaining RP knowledge and skills: addressing retention, development and career progression. We must support the flow of students into science-based topics and attractively promote our profession. The availability of university and other training courses, together with research opportunities, must be supported. Mentoring of young professionals is key, supported by empathetic seniors in the profession. The overall challenge necessitates cooperation across a wide range of organisations at both international and national level.